Induction and maintenance of CX3CR1-intermediate peripheral memory CD8+ T cells by persistent viruses and vaccines - Gordon, C; Lee, L; Swadling, L; Hutchings, C; Zinser, M; Highton, A; Capone, S; Folgori, A; Barnes, E; Klenerman, P (Cell Press, 2018)
The induction and maintenance of T cell memory is critical to the success of vaccines. A recently described subset of memory CD8+ T cells defined by intermediate expression of the chemokine receptor CX3CR1 was shown to have self-renewal, proliferative, and tissue-surveillance properties relevant to vaccine-induced memory. We tracked these cells when memory is sustained at high levels: memory inflation induced by cytomegalovirus (CMV) and adenovirus-vectored vaccines. In mice, both CMV and vaccine-induced inflationary T cells showed sustained high levels of CX3R1int cells exhibiting an effector-memory phenotype, characteristic of inflationary pools, in early memory. In humans, CX3CR1int CD8+ T cells were strongly induced following adenovirus-vectored vaccination for hepatitis C virus (HCV) (ChAd3-NSmut) and during natural CMV infection and were associated with a memory phenotype similar to that in mice. These data indicate that CX3CR1int cells form an important component of the memory pool in response to persistent viruses and vaccines in both mice and humans.